The Extent Integration Of Professional Practices Between The Internal And External Auditors In The Algerian Environment – Attitudes On A Sample Of Professionals In Algeria. - baalla, aya; gamane, mustapha (Journal of Research in Finance and Accounting, 2025)
The study investigates the level of professional collaboration between internal and external auditors in Algeria. It examines integration concepts and mechanisms, identifying areas where collaboration occurs. A questionnaire was distributed to accounting experts in M'SILA, DJELFA, and SETIF. The study revealed that there is a consciousness about the integration value by Algerian internal and external auditors, but the reality of its application does not reach a high level and is still slight as a result of the trust gap between them.